The effect of swine insurance participation on swine production efficiency: Evidence from China - Jingyue Feng; Shan He; Chunli Wan; Jia Liu; Fengjie Xie (PLoS ONE, 2025)
How does swine insurance affect the swine production efficiency in China? We focus on micro-survey data from 582 swine farmers in Liaoning Province, and uses the propensity score matching method (PSM) and mediated effects model for the empirical examination. The results indicate that swine insurance positively impacts production efficiency, compared to uninsured farmers, those who participate in swine insurance exhibit a 4.7% improvement in production efficiency. Additionally, the estimations from the mediated effects models indicate that swine insurance significantly enhances swine production efficiency by influencing risk appetite, production decision and technology adoption. Furthermore, the heterogeneity analysis revealed that the positive effect of swine insurance on production efficiency becomes more pronounced as the scale of farmers’ swine production expands. Apart from this, the correlation between swine insurance coverage level and production efficiency reveals a significant U-shaped curve. These findings provide valuable insights for improving the swine insurance system and fostering the growth of the swine industry.